Assessment of the ability of V920 recombinant vesicular stomatitis-Zaire ebolavirus vaccine to replicate in relevant arthropod cell cultures and vector species - Nicholas A. Bergren; Megan R. Miller; Thomas P. Monath; Rebekah C. Kading (Taylor & Francis Group, 2018)
V920, rVSVΔG-ZEBOV-GP, is a recombinant vesicular stomatitis-Zaire ebolavirus vaccine which has shown an acceptable safety profile and provides a protective immune response against Ebola virus disease (EVD) induced by Zaire ebolavirus in humans. The purpose of this study was to determine whether the V920 vaccine is capable of replicating in arthropod cell cultures of relevant vector species and of replicating in live mosquitoes. While the V920 vaccine replicated well in Vero cells, no replication was observed in Anopheles or Aedes mosquito, Culicoides biting midge, or Lutzomyia sand fly cells, nor in live Culex or Aedes mosquitoes following exposure through intrathoracic inoculation or feeding on a high-titer infectious blood meal. The insect taxa selected for use in this study represent actual and potential epidemic vectors of VSV. V920 vaccine inoculated into Cx. quinquefasciatus and Ae. aegypti mosquitoes demonstrated persistence of replication-competent virus following inoculation, consistent with the recognized biological stability of the vaccine, but no evidence for active virus replication in live mosquitoes was observed. Following administration of an infectious blood meal to Ae. aegypti and Cx. quinquefasciatus mosquitoes at a titer several log10 PFU more concentrated than would be observed in vaccinated individuals, no infection or dissemination of V920 was observed in either mosquito species. In vitro and in vivo data gathered during this study support minimal risk of the vector-borne potential of the V920 vaccine.